Trabalhadores perpétuos: Estudo sobre a reprodução do trabalho dos(as) motoristas das empresas Uber e 99pop - Oliveira, Izadora Lemes de (2024)
There is great interest in research on the reality of drivers for app-based companies. However, research on the social reproduction of this work has still been little studied. In this sense, this research sought to investigate workers outside of vehicles who are also involved in the uberization of work. This is a qualitative study, whose general objective was to identify who is responsible for the social reproduction of the work of drivers for the companies Uber and 99POP. To this end, a participatory survey was conducted to select the drivers and the family member responsible for domestic and care work in their homes. Subsequently, semi structured interviews were conducted with the drivers and the people indicated, through the application of scripts inspired by research on time use. Among the cases analyzed, the social reproduction of the work of the drivers studied is concentrated in female figures. Furthermore, there is a pattern among families with dependents and another among families without dependents, with more acute cases of work intensification and appropriation of women's work in families whose members are black and have dependents. In the group of participants without dependents, all white, there is a greater attachment to the ideology of entrepreneurship. The results revealed asymmetries of class, gender and race and allowed reflections on the uberization of work that goes beyond the condition of platform drivers, as it also attracts family members responsible for the social reproduction of the work of the drivers participating in this research. Finally, it is understood that uberization has appropriated the social reproduction of work and, as a consequence, transformed drivers and family members into perpetual workers.